2011
DOI: 10.1007/s00468-011-0596-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between photosystem II efficiency and photochemical reflectance index under different levels of illumination: comparison among species grown at high- and low elevations through different seasons

Abstract: Previously, we found a significant association between photosystem II efficiency (I broken vertical bar PSII) and photochemical reflectance index (PRI) measured at predawn among different species at different elevations and throughout several seasons. However, this relationship has not been evaluated under varied levels of illumination. Here, we used the Taiwan species Pinus taiwanensis (a conifer distributed at 750-3,000 m a.s.l.), Stranvaesia niitakayamensis (an evergreen tree, 1,700-3,100 m) and two Miscant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…Similar response was found by Stylinski et al (2000) who reported that an increase in photosynthetic electron rate brought an increase in PRI in Quercus pubescenc leaves exposed to natural and elevated CO 2 concentrations. Positive relation between Φ PSII and PRI was also found in grasses (Weng et al 2012) as well as two srubs Baccharis halimifolia and Myrica cerifera exposed to salt stress (Zinnert et al 2012).…”
Section: Discussionmentioning
confidence: 81%
“…Similar response was found by Stylinski et al (2000) who reported that an increase in photosynthetic electron rate brought an increase in PRI in Quercus pubescenc leaves exposed to natural and elevated CO 2 concentrations. Positive relation between Φ PSII and PRI was also found in grasses (Weng et al 2012) as well as two srubs Baccharis halimifolia and Myrica cerifera exposed to salt stress (Zinnert et al 2012).…”
Section: Discussionmentioning
confidence: 81%
“…It is important that intensities of the reflected light can be used for the calculation of reflectance indices, because analysis based on these indices has low errors in comparison with the analysis of absolute values of the reflected light [10]. It is known that reflectance indices permit to estimate different characteristics of plants, including the growth of biomass [21], the photosynthetic efficiency and photosynthetic stress responses [16][17][18][19][20]23,33,58,70,71], the changes in biochemical compositions [29][30][31][32][33][34][35][36], the transpiration [72,73], the isoprene emission [20,24,25], etc.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous investigations that analyze the relations of the modifications of reflectance with the responses of physiological processes (including photosynthesis and its regulation [16][17][18][19][20], growth [21], water exchange [14,22,23], isoprene emission [20,24,25], electrical activity [26][27][28], etc. ), the changes in biochemical content (including concentrations of chlorophylls [29][30][31], carotenoids [32][33][34], nitrogen compositions [35,36], etc.…”
Section: Introductionmentioning
confidence: 99%
“…PRI values during growth were lower for sunlit than shaded leaves [83,112] and were higher for dark-green than either light-or yellow-green leaves [83,87]. PSII efficiency could not be efficiently tracked by PRI in varying light intensities, seasons and leaf colors due to the influence of chlorophyll, low temperature at night or low illumination on reflectance, which inhibit the epoxidation of the xanthophyllic cycle and retain more xanthophyllic pigments [87,113]. Likewise, the tracking of seasonal levels of Chlorophyll a/b (Chl a/b) using PRI was affected by high non-photochemical dissipation from the senescence of the vegetation and drought stress in desert species during growth [114].…”
Section: Foliar Levelmentioning
confidence: 99%
“…The accuracy of the simulated PRI from ACRM (A Markov chain Analytical two-layer Canopy Reflectance Model) was affected by canopy structural change and thus led to inaccurate estimates of RUE and GPP [83]. Empirical regression models were effectively used to assess PRI and ecophysiological variation [87,109,113,124]. Devising a valid model is therefore important for accurately estimating PRI and providing a continuous assessment of GPP.…”
Section: Modelingmentioning
confidence: 99%